Abra State Institute of Science and Technology Bangued Campus (ASIST-BC) Library - Balderas, Sharone Benedicta B. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2015)
This descriptive research assessed tha Abra State Institute of Science and Technology-Bangued Campus (ASIST-BC) Library in terms of status and extent of manifestation of the AACCUP Standards along the seven dimensions of the library. The AACCUP questionnaire was utilized for the data gathering on the status and perception of the eveluators. Data were treated using the weighted mean and ranking.
Bibliography: pages 89-92.
CHED-La Union
Keywords: Libraries; Colleges and universities